The animosity inside the armed forces: monitoring and expurgation in the military commands (Tempo e Argumento, 2009)
The present article has as objective to analyze the practice of monitoring and repression of the Secret Service of the Social Order and Political Police of São Paulo (DOPS-SP), through the analysis of their reports during the period of 1950 -1961, giving emphasis their action under the command of the Armed Forces. The infiltration of their agents in the summit of the militaries who, congregated in the Military Club, debated the alternatives for the national development and the entailing of this repressive system with the political segments which were subordinated to the sectors of the dependent bourgeoisie - whose monopoly of domination was threatened by the magnifying of the civil rights - sets off a persecution and expurgations against militaries as well as of the organizations considered pernicious to the continuity of the monopolistic dependent capitalism, supported by this institutionalized bourgeois’ autocracy.
Keywords: bourgeois’ autocracy; armed forces; DOPS-SP